Performance evaluation of Bacteroidales genetic markers for human and animal microbial source tracking in tropical agricultural watersheds - Pornjira Somnark (2019)
© 2018 Elsevier Ltd Microbial source tracking (MST) DNA-based assays have been used to successfully solve fecal pollution problems in many countries, particularly in developed nations. However, their application in developing countries has been limited but continues to increase. In this study, sixteen endpoint and quantitative PCR (qPCR) assays targeting universal and human-, swine-, and cattle-specific Bacteroidales gene markers were modified for endpoint PCR, evaluated for their performance with sewage and fecal samples from the Tha Chin watershed and subsequently validated with samples from the Chao Phraya watershed, Thailand. Sample sizes of 81 composite samples (from over 1620 individual samples) of farm animals of each type as well as 19 human sewage samples from the Tha Chin watershed were calculated using a stratified random sampling design to achieve a 90% confidence interval and an expected prevalence (i.e., desired assay's sensitivity) of 0.80. The best universal and human-, swine-, and cattle-specific fecal markers were BacUni EP, HF183/BFDrev EP, Pig-2-Bac EP, and Bac3 assays, respectively. The detection limits for these assays ranged from 30 to 3000 plasmid copies per PCR. The positive predictive values were high in universal and swine- and cattle-specific markers (85–100%), while the positive predictive value of the human-specific assay was 52.2%. The negative predictive values in all assays were relatively high (90.8–100%). A suite of PCR assays in Thailand was established for potential MST use in environmental waters, which supports the worldwide applicability of Bacteroidales gene markers. This study also emphasizes the importance of using a proper sample size in assessing the performance of MST markers in a new geographic region. The successful validation of the Bacteroidales fecal markers for MST with fecal samples in Southeast Asia strongly supports their global use, with an emphasis on significant sample size calculation as a vital approach for evaluating MST markers.